Lanthanum polystyrene sulfonate sheet and preparation method thereof
By using microcrystalline cellulose and hydroxypropyl methyl cellulose as disintegrants in polystyrene lanthanum sulfonate tablets, combined with coating technology, the problem of poor compliance with lanthanum carbonate chewable tablets in patients with chronic renal failure without chewing ability is solved, and the rapid absorption and blood phosphorus reduction effect of polystyrene lanthanum sulfonate micropowder is achieved.
Patent Information
- Application Number
- CN202310068861.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-02-06
AI Technical Summary
Patients with chronic renal failure who have no chewing ability have poor compliance with lanthanum carbonate chewable tablets, which is difficult to effectively reduce blood phosphorus levels.
Polystyrene lanthanum sulfonate tablets are used to promote rapid disintegration of the powder in the oral cavity by using microcrystalline cellulose and hydroxypropyl methyl cellulose in the powder. Combined with coating technology, the structural strength and transportation stability of the tablet are improved.
The rapid dispersion and absorption of polystyrene lanthanum sulfonate micropowder in the oral cavity is achieved, which is convenient for patients without chewing ability to take it, effectively reduce the blood phosphorus level, and improve the bioavailability and transportation stability of the tablet by adding vitamin C and modified chitosan.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of pharmaceutical preparations, and in particular to a lanthanum polystyrene sulfonate tablet and a preparation method thereof. Background Art
[0002] Chronic kidney disease is a chronic systemic disease or a chronic kidney disease that affects 6-10% of the world's population. As the patient's kidney function declines, it will cause many complications, among which hyperphosphatemia has become one of the most common complications of chronic kidney disease.
[0003] Lanthanum polystyrene sulfonate is a drug for treating hyperphosphatemia in chronic renal failure. Lanthanum polystyrene sulfonate is a non-aluminum, non-calcium high-molecular-weight phosphate binder. After oral administration, it can release lanthanum ions in the digestive tract. The free lanthanum ions combine with phosphates in food to form insoluble phosphate complexes to inhibit the absorption of phosphate, thereby reducing the serum phosphate level in patients with hyperphosphatemia, and has a significant effect in lowering blood phosphorus.
[0004] In 2004, Shire launched lanthanum carbonate chewable tablets in the United States. The active ingredient is lanthanum carbonate hydrate, with the general structural formula: La2(CO3)3·XH2O, X represents 4-5 moles, and the relative molecular weight is 529.9 (containing 4 moles of water). However, this product is an oral medication and must be chewed before swallowing. For patients with chronic renal failure who are unable to chew, the compliance of chewable tablets is poor. Summary of the invention
[0005] In order to improve the problem of poor compliance of chewable tablets for patients with chronic renal failure who are unable to chew, the present application provides a lanthanum polystyrene sulfonate tablet and a preparation method thereof.
[0006] The present application provides a lanthanum polystyrene sulfonate sheet, which adopts the following technical solution:
[0007] A lanthanum polystyrene sulfonate tablet comprises a coating and a powder, wherein the powder comprises the following raw materials in parts by weight: 30-50 parts of lanthanum polystyrene sulfonate micropowder, 10-20 parts of a filler, 15-25 parts of microcrystalline cellulose, 8-15 parts of hydroxypropyl methylcellulose, 0.1-0.6 parts of a flavoring agent, 0.3-0.8 parts of a lubricant and 0.5-0.9 parts of vitamin C.
[0008] By adopting the above technical solution, microcrystalline cellulose has a sponge-like porous tubular structure. When it meets water, water molecules enter the interior of the tablet, destroying the hydrogen bonds between the microcrystals, causing the powder to disintegrate rapidly, thereby allowing the polystyrene lanthanum sulfonate micropowder to disperse in the mouth. Chronic renal failure patients who are unable to chew can swallow it directly or take it with water, which is convenient for patients to take, thereby allowing the polystyrene lanthanum sulfonate micropowder to exert its medicinal effect.
[0009] Hydroxypropyl methylcellulose has strong hygroscopicity and swells but does not dissolve in water. It has a synergistic effect with microcrystalline cellulose. Water molecules destroy the hydrogen bonds between microcrystals, while hydroxypropyl methylcellulose swells in water, thereby accelerating the breaking rate of hydrogen bonds between microcrystals, further improving the disintegration efficiency of tablets. In addition, hydroxypropyl methylcellulose has a rough surface structure, which can enhance the mosaic effect between tablet component particles, improve the viscosity and smoothness of the tablet, and thus improve the adhesion between the tablet components, which helps to improve the structural strength of the tablet and reduce the chance of tablets breaking during transportation.
[0010] Patients with chronic renal failure who are unable to chew often undergo hemodialysis while taking medications. Due to insufficient food intake, metabolic changes and vitamin loss through dialysis, hemodialysis patients will suffer from vitamin deficiency if not supplemented in time. Therefore, lanthanum polystyrene sulfonate tablets contain vitamin C to help patients supplement vitamin C in time and avoid nutritional deficiencies.
[0011] The lanthanum polystyrene sulfonate tablets include a coating and a powder. The coating wraps the powder, thereby further reducing the vibration or friction of the tablets during transportation, thereby reducing the damage of the tablets.
[0012] Preferably, the pretreatment method of the lanthanum polystyrene sulfonate powder comprises the following steps:
[0013] (1) grinding polystyrene lanthanum sulfonate powder at a temperature of 30-40° C. to obtain a particle size of 20-30 μm to obtain polystyrene lanthanum sulfonate powder, then adding anhydrous ethanol and mixing evenly to obtain a polystyrene lanthanum sulfonate solution;
[0014] (2) The lanthanum polystyrene sulfonate solution obtained in step (1) is subjected to a heat treatment, heated and stirred at a temperature of 60-80° C. for 30-45 minutes, and then put into a jet mill and crushed to a particle size of 2-8 μm to obtain lanthanum polystyrene sulfonate powder.
[0015] By adopting the above technical scheme, the lanthanum polystyrene sulfonate powder is crushed to a particle size of 20-30 μm, which helps to improve the dissolution rate of the lanthanum polystyrene sulfonate tablets and increase their bioavailability. Crushing at a temperature of 30-40°C helps to improve the biological activity of the lanthanum polystyrene sulfonate powder and can be crushed to obtain a finer particle size; then the lanthanum polystyrene sulfonate powder is dispersed in anhydrous ethanol, the lanthanum polystyrene sulfonate powder fully expands in the anhydrous ethanol and is dispersed, the molecular chain state is fully opened, and after heating and stirring treatment, the biological activity of the lanthanum polystyrene sulfonate powder is further improved, the particle size of the lanthanum polystyrene sulfonate powder is reduced, which helps to be subsequently put into a gas flow mill for crushing, prevents the electrostatic effect of the lanthanum polystyrene sulfonate powder with a smaller particle size from being enhanced during crushing, and the particles are agglomerated, thereby improving the crushing efficiency, crushing to a particle size of 2-8 μm, and using microcrystalline cellulose as a disintegrant to accelerate the dissolution and solubility of the lanthanum polystyrene sulfonate powder, which helps to fully absorb it in subsequent patients.
[0016] Preferably, in step (1), the mass ratio of the lanthanum polystyrene sulfonate powder to anhydrous ethanol is 1:0.8-1.2.
[0017] By adopting the above technical solution, the mass ratio of polystyrene lanthanum sulfonate powder to anhydrous ethanol is limited within a certain range, which helps to fully expand the polystyrene lanthanum sulfonate powder, thereby improving the biological activity of the polystyrene lanthanum sulfonate powder and helping to improve the particle size of subsequent powders.
[0018] Preferably, in step (2), the powder is crushed in a jet mill with a feed rate of 0.3-0.8 kg / h and a crushing pressure of 1-2 MPa.
[0019] By adopting the above technical solution and setting a suitable feed rate and crushing pressure, it is helpful to obtain lanthanum polystyrene sulfonate powder with a more uniform particle size.
[0020] Preferably, the coating comprises the following raw materials in parts by weight: 10-20 parts of sodium hydroxypropyl methylcellulose, 8-15 parts of polyvinyl alcohol, 3-5 parts of xylitol, 8-12 parts of malic acid, 10-15 parts of maltodextrin, and 6-10 parts of modified chitosan.
[0021] By adopting the above technical scheme, sodium hydroxypropyl methylcellulose is used as an emulsifier, thickener, and adhesive, polyvinyl alcohol is used as a film-forming material, and has good film-forming properties to form a skeleton structure. Polyvinyl alcohol and malic acid are mixed to make the formed skeleton structure have a larger pore size, and modified chitosan is added to further improve the skeleton structure, forming a three-dimensional skeleton structure, further improving the structural stability and mechanical properties of the coating. At the same time, sodium hydroxypropyl methylcellulose and maltodextrin further increase the viscosity of the system and further enhance the stability of the skeleton structure. When the tablets are in the process of transportation, the setting of the coating reduces the probability of the tablets breaking due to collision or friction. In addition, maltodextrin contains a large amount of sugars, and also contains certain vitamins and trace elements, which can promote the normal metabolism and metabolism of the human body, and help supplement the vitamins and trace elements lacking in the body of dialysis patients.
[0022] Preferably, the preparation method of the modified chitosan comprises the following steps:
[0023] (1) Dissolve chitosan in oxalic acid and stir at 60-70°C for 30-45 minutes to prepare a chitosan solution;
[0024] (2) The chitosan solution obtained in step (1), apple fiber and sodium alginate are mixed, stirred for 20-30 minutes, cooled, recrystallized and dried to obtain modified chitosan.
[0025] By adopting the above technical scheme, chitosan is dissolved in oxalic acid in a viscous state, is a positively charged polyelectrolyte, and has strong adsorption. Sodium alginate is dissolved in the chitosan solution, and sodium alginate gradually forms alginate gel. The alginate gel has a certain strength and good toughness. It is mixed with the chitosan solution to increase the network structure of chitosan, thereby improving the mechanical properties of chitosan. Apple fiber is a water-soluble fiber. Apple fiber is loaded on the network structure of chitosan, which further enhances the structural strength of chitosan, thereby improving the structural strength of subsequent coatings and reducing the chance of subsequent tablet grinding. In addition, apple fiber contains a large amount of nutrient-rich cellulose, which can accelerate metabolism and prevent fat accumulation, has a good lipid-lowering effect, can accelerate metabolism, reduce fat, and help subsequent dialysis patients to maintain better physical function.
[0026] Preferably, the filler is one or more of mannitol, maltose, glucose, lactose and dextrin.
[0027] Preferably, the flavoring agent is one or more of mint flavor, strawberry flavor, watermelon flavor, orange flavor and pineapple flavor.
[0028] Preferably, the lubricant is one or more of talc, magnesium stearate, calcium stearate, polyethylene glycol and magnesium lauryl sulfate.
[0029] In a second aspect, the present application also provides a method for preparing lanthanum polystyrene sulfonate sheets, comprising the following steps:
[0030] S1, mixing lanthanum polystyrene sulfonate powder, filler, microcrystalline cellulose, hydroxypropyl methylcellulose, flavoring agent, lubricant and vitamin C uniformly, granulating with ethanol as a wetting agent, drying, tableting, and obtaining tablets;
[0031] S2, mixing sodium hydroxypropyl methylcellulose, polyvinyl alcohol, xylitol, malic acid, maltodextrin and modified chitosan to obtain a coating mixture;
[0032] S3. The tablets obtained in step S1 and the coating mixture obtained in step S2 are subjected to a coating process. The main technical parameters of the coating process are: outlet air temperature 40-50° C., inlet air 50-60° C., spray gun pressure 0.3-0.4 MPa, and peristaltic pump 110-120 r / min.
[0033] In summary, this application has the following beneficial effects:
[0034] 1. In the present application, microcrystalline cellulose has a sponge-like porous tubular structure. When it comes into contact with water, water molecules enter the interior of the tablet, destroying the hydrogen bonds between the microcrystals, causing the powder to disintegrate rapidly, thereby causing the polystyrene lanthanum sulfonate micropowder to disperse in the oral cavity. Patients with chronic renal failure who are unable to chew can swallow it directly or take it with water, which is convenient for patients to take, thereby allowing the polystyrene lanthanum sulfonate micropowder to exert its medicinal effect.
[0035] 2. In the present application, hydroxypropyl methylcellulose has strong hygroscopicity, swells in water but does not dissolve, and has a synergistic effect with microcrystalline cellulose. Water molecules destroy the hydrogen bonds between microcrystals, and hydroxypropyl methylcellulose swells in water, thereby accelerating the speed of breaking the hydrogen bonds between microcrystals, further improving the disintegration efficiency of the tablet. In addition, hydroxypropyl methylcellulose has a rough surface structure, which can enhance the mosaic effect between the tablet component particles, improve the viscosity and smoothness of the tablet, and then improve the adhesion between the tablet components, which helps to improve the structural strength of the tablet and reduce the probability of tablet breakage during transportation.
[0036] 3. In the present application, patients with chronic renal failure who are unable to chew are often accompanied by hemodialysis while taking medications. Due to insufficient food intake, metabolic changes and vitamin loss through dialysis, dialysis patients will suffer from vitamin deficiency if not supplemented in time. Therefore, the lanthanum polystyrene sulfonate tablets contain vitamin C to help patients supplement vitamin C in time and avoid nutritional deficiencies. In addition, the lanthanum polystyrene sulfonate tablets include a coating and a powder. The coating wraps the powder, further reducing the vibration or friction of the tablets during transportation, thereby reducing the damage of the tablets. DETAILED DESCRIPTION
[0037] The present application is further described in detail below with reference to the embodiments.
[0038] The raw materials used in the examples and comparative examples can all be obtained from the market, wherein the filler is mannitol, the flavoring agent is mint essence, and the lubricant is talcum powder.
[0039] Preparation of Lanthanum Polystyrene Sulfonate Powder
[0040] Preparation Example 1-1
[0041] The pretreatment method of lanthanum polystyrene sulfonate powder comprises the following steps:
[0042] (1) 5 g of polystyrene lanthanum sulfonate powder is crushed at a temperature of 30° C. to obtain a particle size of 20-30 μm to obtain polystyrene lanthanum sulfonate powder, and then anhydrous ethanol is added and mixed to obtain a polystyrene lanthanum sulfonate solution; wherein the mass ratio of the polystyrene lanthanum sulfonate powder to the anhydrous ethanol is 1:1.
[0043] (2) The polystyrene lanthanum sulfonate solution obtained in step (1) is subjected to heat treatment, heated and stirred at a temperature of 60-80° C. for 30-45 min, and then put into a jet mill and crushed to a particle size of 2-8 μm to obtain polystyrene lanthanum sulfonate powder, wherein the feed rate in the jet mill is 0.3 kg / h and the crushing pressure is 2 MPa.
[0044] Preparation Example 1-2
[0045] The pretreatment method of lanthanum polystyrene sulfonate powder comprises the following steps:
[0046] (1) 6 g of polystyrene lanthanum sulfonate powder is crushed at a temperature of 40° C. to obtain a particle size of 20-30 μm to obtain polystyrene lanthanum sulfonate powder, and then anhydrous ethanol is added and mixed to obtain a polystyrene lanthanum sulfonate solution; wherein the mass ratio of the polystyrene lanthanum sulfonate powder to the anhydrous ethanol is 1:0.8.
[0047] (2) The polystyrene lanthanum sulfonate solution obtained in step (1) is subjected to a heat treatment, heated and stirred at a temperature of 60-80° C. for 30-45 min, and then put into a jet mill and crushed to a particle size of 2-8 μm to obtain polystyrene lanthanum sulfonate powder, wherein the powder is crushed in the jet mill at a feed rate of 0.8 kg / h and a crushing pressure of 1 MPa.
[0048] Preparation Example 1-3
[0049] The difference from Preparation Example 1-1 is that in step 1), the pulverization is carried out at a temperature of 25°C.
[0050] Preparation Example 1-4
[0051] The difference from Preparation Example 1-1 is that in step 1), no anhydrous ethanol is added.
[0052] Preparation Example 1-5
[0053] The difference from Preparation Example 1-1 is that the mass ratio of lanthanum polystyrene sulfonate powder to anhydrous ethanol is 1:1.2.
[0054] Preparation Example 1-6
[0055] The difference from Preparation Example 1-1 is that the mass ratio of lanthanum polystyrene sulfonate powder to anhydrous ethanol is 1:1.5.
[0056] Preparation example of modified chitosan
[0057] Preparation Example 2-1
[0058] The preparation method of modified chitosan comprises the following steps:
[0059] (1) Dissolve 3 g of chitosan in 50 mL of 20% oxalic acid and stir at 60 °C for 35 min to prepare a chitosan solution;
[0060] (2) The chitosan solution obtained in step (1), 1 g of apple fiber and 1.5 g of sodium alginate were mixed, stirred for 25 min, cooled, recrystallized and dried to obtain modified chitosan.
[0061] Preparation Example 2-2
[0062] The difference from Preparation Example 2-1 is that in step (2), apple fiber is not added.
[0063] Preparation Example 2-3
[0064] The difference from Preparation Example 2-1 is that in step (2), sodium alginate is not added. Example
[0065] Example 1
[0066] A lanthanum polystyrene sulfonate tablet comprises a coating and a powder, wherein the powder comprises the following raw materials by weight: 4 g of lanthanum polystyrene sulfonate micropowder, 15 g of a filler, 20 g of microcrystalline cellulose, 12 g of hydroxypropyl methylcellulose, 0.4 g of a flavoring agent, 0.5 g of a lubricant and 0.7 g of vitamin C.
[0067] The coating includes the following raw materials by weight: 15 g of sodium hydroxypropyl methylcellulose, 12 g of polyvinyl alcohol, 4 g of xylitol, 10 g of malic acid, 12 g of maltodextrin, and 8 g of modified chitosan.
[0068] The preparation method of the above-mentioned lanthanum polystyrene sulfonate sheet comprises the following steps:
[0069] S1, mixing lanthanum polystyrene sulfonate powder, filler, microcrystalline cellulose, hydroxypropyl methylcellulose, flavoring agent, lubricant and vitamin C uniformly, granulating with ethanol as a wetting agent, drying, tableting, and obtaining tablets;
[0070] S2, mixing sodium hydroxypropyl methylcellulose, polyvinyl alcohol, xylitol, malic acid, maltodextrin and modified chitosan to obtain a coating mixture;
[0071] S3. The tablets obtained in step S1 and the coating mixture obtained in step S2 are subjected to a coating process. The main technical parameters of the coating process are: outlet air temperature 45° C., inlet air temperature 55° C., spray gun pressure 0.3 MPa, and peristaltic pump 120 r / min.
[0072] The pretreatment of lanthanum polystyrene sulfonate powder was prepared by using Preparation Example 1-1; the modified chitosan was prepared by using Preparation Example 2-1.
[0073] Example 2
[0074] A lanthanum polystyrene sulfonate sheet is different from Example 1 in that the lanthanum polystyrene sulfonate powder is pretreated using Preparation Example 1-2.
[0075] Example 3
[0076] A lanthanum polystyrene sulfonate sheet is different from Example 1 in that the lanthanum polystyrene sulfonate powder is pretreated using Preparation Example 1-3.
[0077] Example 4
[0078] A lanthanum polystyrene sulfonate sheet is different from Example 1 in that the lanthanum polystyrene sulfonate powder is pretreated using Preparation Examples 1-4.
[0079] Example 5
[0080] A lanthanum polystyrene sulfonate sheet is different from Example 1 in that the lanthanum polystyrene sulfonate powder is pretreated using Preparation Examples 1-5.
[0081] Example 6
[0082] A lanthanum polystyrene sulfonate sheet is different from Example 1 in that the lanthanum polystyrene sulfonate powder is prepared by pretreatment using Preparation Examples 1-6.
[0083] Example 7
[0084] A lanthanum polystyrene sulfonate sheet, which is different from Example 1 in that the modified chitosan is prepared using Preparation Example 2-2.
[0085] Example 8
[0086] A lanthanum polystyrene sulfonate sheet, which is different from Example 1 in that the modified chitosan is prepared using Preparation Example 2-3.
[0087] Example 9
[0088] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that the powder comprises the following raw materials by weight: 30 g of lanthanum polystyrene sulfonate powder, 10 g of filler, 15 g of microcrystalline cellulose, 8 g of hydroxypropyl methylcellulose, 0.1 g of flavoring agent, 0.3 g of lubricant and 0.5 g of vitamin C.
[0089] Example 10
[0090] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that the powder comprises the following raw materials by weight: 50 g of lanthanum polystyrene sulfonate powder, 20 g of filler, 25 g of microcrystalline cellulose, 15 g of hydroxypropyl methylcellulose, 0.6 g of flavoring agent, 0.8 g of lubricant and 0.9 g of vitamin C.
[0091] Embodiment 11
[0092] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that the coating comprises the following raw materials by weight: 10 g of sodium hydroxypropyl methylcellulose, 8 g of polyvinyl alcohol, 3 g of xylitol, 8 g of malic acid, 10 g of maltodextrin, and 6 g of modified chitosan.
[0093] Example 12
[0094] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that the coating comprises the following raw materials by weight: 20 g of sodium hydroxypropyl methylcellulose, 15 g of polyvinyl alcohol, 5 g of xylitol, 12 g of malic acid, 15 g of maltodextrin, and 10 g of modified chitosan.
[0095] Embodiment 13
[0096] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that the coating comprises the following raw materials by weight: 8 g of sodium hydroxypropyl methylcellulose, 17 g of polyvinyl alcohol, 1 g of xylitol, 15 g of malic acid, 8 g of maltodextrin, and 4 g of modified chitosan.
[0097] Embodiment 14
[0098] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that the coating comprises the following raw materials by weight: 25 g of sodium hydroxypropyl methylcellulose, 6 g of polyvinyl alcohol, 7 g of xylitol, 6 g of malic acid, 17 g of maltodextrin, and 12 g of modified chitosan.
[0099] Embodiment 15
[0100] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that malic acid is not added to the coating raw materials.
[0101] Example 16
[0102] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that no modified chitosan is added to the coating raw materials.
[0103] Embodiment 17
[0104] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that polyvinyl alcohol is not added to the coating raw materials.
[0105] Embodiment 18
[0106] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that an equal amount of chitosan is used in the coating raw material instead of modified chitosan.
[0107] Comparative Example
[0108] Comparative Example 1
[0109] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that the powder comprises the following raw materials by weight: 25 g of lanthanum polystyrene sulfonate powder, 8 g of filler, 30 g of microcrystalline cellulose, 6 g of hydroxypropyl methylcellulose, 0.05 g of flavoring agent, 0.9 g of lubricant and 0.4 g of vitamin C.
[0110] Comparative Example 2
[0111] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that the powder comprises the following raw materials by weight: 55 g of lanthanum polystyrene sulfonate powder, 25 g of filler, 12 g of microcrystalline cellulose, 17 g of hydroxypropyl methylcellulose, 0.8 g of flavoring agent, 0.2 g of lubricant and 1.2 g of vitamin C.
[0112] Comparative Example 3
[0113] A lanthanum polystyrene sulfonate tablet, which is different from Example 1 in that an equal amount of polyvinyl pyrrolidone is used instead of hydroxypropyl methylcellulose.
[0114] Comparative Example 4
[0115] A lanthanum polystyrene sulfonate tablet, which differs from Example 1 in that vitamin C is not added.
[0116] Comparative Example 5
[0117] A lanthanum polystyrene sulfonate tablet, which differs from Example 1 in that no coating is added.
[0118] Performance testing
[0119] The coatings prepared in the examples and comparative examples were subjected to disintegration time determination and mechanical property tests, and the lanthanum polystyrene sulfonate tablets were subjected to disintegration time determination.
[0120] Determination of dissolution time of coating: Referring to the disintegration time test method of tablets in the fourth general rule of the 2015 edition of the Chinese Pharmacopoeia, the coating samples prepared in Examples 1-2, 7-8 and 11-18 were cut into 1 cm 2 The time it takes for the product to completely dissolve was observed for the films of different sizes. The test results are shown in Table 1.
[0121] Coating tensile property test: The coatings prepared in Examples 1-18 and Comparative Examples 1-4 were cut into specimens of 100 mm×20 mm in size, and the tensile properties were tested on a tensile strength tester.
[0122] Specifically, place the sample in the upper and lower clamps of the tensile strength tester, so that the center line of the sample and the upper and lower clamps coincides, the clamps are appropriately tight, and the distance between the two clamps is 60mm. Start the test machine at a speed of 100±10mm / min, and read the tensile strength and elongation after the sample breaks.
[0123] Determination of the dissolution time of lanthanum polystyrene sulfonate tablets: Referring to the disintegration time test method of tablets in the fourth general rule 0921 of the 2015 edition of the Chinese Pharmacopoeia, the disintegration time of lanthanum polystyrene sulfonate tablets prepared in Examples 1-6, Examples 9-10 and Comparative Examples 1-3 was determined to observe the time for complete dissolution of the product. The test results are shown in Table 1.
[0124] Table 1 Tests of Examples and Comparative Examples
[0125] Coating disintegration time / s Coating tensile strength / N Coating breaking rate / % Tablet disintegration time / s Example 1 8 16 25 10 Example 2 9 15 24 11 Example 3 \ \ \ 16 Example 4 \ \ \ 17 Example 5 \ \ \ 11 Example 6 \ \ \ 14 Example 7 9 11 20 Example 8 8 10 18 Example 9 \ \ \ 11 Example 10 \ \ \ 10 Embodiment 11 8 15 24 \ Example 12 9 14 23 \ Embodiment 13 12 12 21 \ Embodiment 14 13 11 22 \ Embodiment 15 18 8 19 \ Example 16 17 7 17 \ Embodiment 17 19 8 16 \ Embodiment 18 11 12 20 \ Comparative Example 1 \ \ \ 15 Comparative Example 2 \ \ \ 16 Comparative Example 3 \ \ \ 18
[0126] As can be seen from Table 1, the lanthanum polystyrene sulfonate tablets prepared in Examples 1-2, 5, 9-10 of the present application have a faster disintegration time limit of 10s, which is convenient for patients with chronic renal failure who have no chewing ability to swallow directly or take it with water, so that the lanthanum polystyrene sulfonate powder can exert its efficacy. At the same time, the coating disintegration time limit tested in Examples 1-2 and 11-12 is 8s or 9s, and the rapid dissolution of the coating contributes to the disintegration of subsequent tablets. The tensile strength of the coating is as high as 16N, and the coating pull-off rate is as high as 25%, indicating that the coating prepared in the present application has good mechanical properties, and in the subsequent transportation of the tablets, the probability of the tablets being broken during transportation is reduced.
[0127] In the pretreatment method of polystyrene lanthanum sulfonate powder in Example 3, the powder was crushed at a temperature of 25°C. As shown in Table 1, the tablet disintegration time was 16s, indicating that crushing at a certain temperature can improve the biological activity of polystyrene lanthanum sulfonate powder, help to crush to obtain finer particle size, and thus improve the disintegration efficiency of subsequent tablets.
[0128] In the pretreatment method of polystyrene lanthanum sulfonate powder in Example 3, no anhydrous ethanol is added. As can be seen from Table 1, the tablet disintegration time is 17s, indicating that anhydrous ethanol can make the polystyrene lanthanum sulfonate powder fully expand and disperse, and the molecular chain state is fully opened, which helps to improve the biological activity of the polystyrene lanthanum sulfonate powder and facilitate the subsequent crushing of the polystyrene lanthanum sulfonate powder.
[0129] Example 6 changes the mass ratio of lanthanum polystyrene sulfonate powder to anhydrous ethanol. As can be seen from Table 1, compared with Example 1 and Example 5, the tablet disintegration time is 14 s, indicating that by limiting the mass ratio of lanthanum polystyrene sulfonate powder to anhydrous ethanol within a certain range, a lanthanum polystyrene sulfonate powder with higher biological activity is obtained, which helps to improve the subsequent disintegration efficiency of the lanthanum polystyrene sulfonate powder.
[0130] In the preparation method of modified chitosan in Example 7, apple fiber is not added, the coating disintegration time is 9s, the coating tensile strength is 11N, and the coating breaking rate is 20%, indicating that apple fiber does not affect the disintegration efficiency of the coating, but significantly affects the mechanical properties of the coating. Apple fiber is loaded on the network structure of chitosan, which further enhances the structural strength of chitosan, thereby improving the structural strength of subsequent coatings and reducing the chance of subsequent tablet grinding.
[0131] In the preparation method of modified chitosan in Example 8, sodium alginate is not added, the coating disintegration time is 8s, the coating tensile strength is 10N, and the coating breaking rate is 18%, indicating that sodium alginate does not affect the disintegration efficiency of the coating, but significantly affects the mechanical properties of the coating. Sodium alginate has good toughness and is mixed with chitosan solution to increase the network structure of chitosan, thereby improving the mechanical properties of chitosan.
[0132] In Examples 13-14, the proportion of each raw material component in the coating was changed. As can be seen from Table 1, the disintegration time of the coating was significantly increased, and the tensile strength and breaking rate of the coating were significantly reduced, indicating that the content of each component of the coating of the present application has a good disintegration time and mechanical properties within a certain range.
[0133] In Example 15, no malic acid is added to the coating raw materials, and the coating disintegration time is 18s, the coating tensile strength is 8N, and the coating pull-off rate is 19%. In Example 16, no modified chitosan is added to the coating raw materials, the coating disintegration time is 17s, the coating tensile strength is 7N, and the coating pull-off rate is 17%. In Example 17, no polyvinyl alcohol is added to the coating raw materials, the coating disintegration time is 19s, the coating tensile strength is 8N, and the coating pull-off rate is 16%. It can be seen that without adding the above single component, the coating disintegration time is significantly increased, the coating tensile strength and the coating pull-off rate are significantly reduced, indicating that the three components all affect the performance of the coating. Polyvinyl alcohol is used as a film-forming material to form a skeleton structure, and malic acid and polyvinyl alcohol are combined to make the formed skeleton structure have a larger pore size. Modified chitosan is added to further improve the skeleton structure to form a three-dimensional skeleton structure, which further improves the structural stability and mechanical properties of the coating.
[0134] In Example 18, the modified chitosan was replaced by an equal amount of chitosan, and the coating disintegration time was significantly increased, and the coating tensile strength and coating break rate were significantly reduced, indicating that the modified chitosan prepared in this application has good comprehensive properties and meets the use requirements of the coating.
[0135] Comparative Example 1-2 changes the content of each component of the powder. As can be seen from Table 1, compared with Example 1-2, the disintegration time is significantly increased, indicating that the content of each component of the powder of the present application has a good disintegration time within a certain range.
[0136] In Comparative Example 3, an equal amount of polyvinyl pyrrolidone is used instead of hydroxypropyl methylcellulose. As can be seen from Table 1, compared with Examples 1-2, the disintegration time is significantly increased, indicating that the hydroxypropyl methylcellulose used in the present application has strong hygroscopicity, swells in water but does not dissolve, and has a synergistic effect with microcrystalline cellulose. Water molecules destroy the hydrogen bonds between the microcrystals, and hydroxypropyl methylcellulose swells in water, thereby accelerating the breaking rate of hydrogen bonds between the microcrystals, further improving the disintegration efficiency of the tablet.
[0137] The lanthanum polystyrene sulfonate tablets prepared in Comparative Example 4 do not contain vitamin C, and dialysis patients are prone to vitamin C deficiency during dialysis, which in turn causes nutritional deficiencies in the body and easily leads to decreased immunity. Therefore, vitamin C is added to the lanthanum polystyrene sulfonate tablets to help patients replenish vitamin C in time and avoid nutritional deficiencies in the body.
[0138] The friability of the lanthanum polystyrene sulfonate tablets prepared in Example 1 and Comparative Example 5 was measured: referring to the friability inspection method for tablets in Part IV of the 2015 edition of the Chinese Pharmacopoeia 0923: take 10 tablets, blow off the powder that falls off the tablets with a hair dryer, weigh them accurately, place them in a cylinder, and rotate them 100 times; take them out, remove the powder in the same way, weigh them accurately, and calculate the weight loss. The test results show that the tablets in Example 1 are intact and have a friability of 0, while the tablets in Comparative Example 5 have broken, cracked or crushed tablets. The friability of the tablets in Comparative Example 5 is 1.2%, indicating that the friability of the lanthanum polystyrene sulfonate tablets prepared in the present application is better than that of Comparative Example 5, and the appearance is complete and convenient for transportation.
[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A lanthanum polystyrene sulfonate sheet, characterized in that: The invention comprises a coating and a powder, wherein the powder comprises the following raw materials in parts by weight: 30-50 parts of lanthanum polystyrene sulfonate powder, 10-20 parts of a filler, 15-25 parts of microcrystalline cellulose, 8-15 parts of hydroxypropyl methylcellulose, 0.1-0.6 parts of a flavoring agent, 0.3-0.8 parts of a lubricant and 0.5-0.9 parts of vitamin C; The pretreatment method of the lanthanum polystyrene sulfonate powder comprises the following steps: (1) grinding polystyrene lanthanum sulfonate powder at a temperature of 30-40° C. to obtain a particle size of 20-30 μm to obtain polystyrene lanthanum sulfonate powder, then adding anhydrous ethanol and mixing evenly to obtain a polystyrene lanthanum sulfonate solution; (2) heating the lanthanum polystyrene sulfonate solution obtained in step (1) at 60-80° C. with stirring for 30-45 min, and then grinding it in a jet mill to a particle size of 2-8 μm to obtain lanthanum polystyrene sulfonate powder; In step (1), the mass ratio of the lanthanum polystyrene sulfonate powder to anhydrous ethanol is 1:0.8-1.2; The coating comprises the following raw materials in parts by weight: 10-20 parts of sodium hydroxypropyl methylcellulose, 8-15 parts of polyvinyl alcohol, 3-5 parts of xylitol, 8-12 parts of malic acid, 10-15 parts of maltodextrin, and 6-10 parts of modified chitosan; The preparation method of the modified chitosan comprises the following steps: (1) Dissolve chitosan in oxalic acid and stir at 60-70°C for 30-45 minutes to prepare a chitosan solution; (2) mixing the chitosan solution obtained in step (1), apple fiber and sodium alginate, stirring for 20-30 minutes, cooling, recrystallizing and drying to obtain modified chitosan; A method for preparing lanthanum polystyrene sulfonate sheets comprises the following steps: S1, mixing lanthanum polystyrene sulfonate powder, filler, microcrystalline cellulose, hydroxypropyl methylcellulose, flavoring agent, lubricant and vitamin C uniformly, granulating with ethanol as a wetting agent, drying, tableting, and obtaining tablets; S2, mixing sodium hydroxypropyl methylcellulose, polyvinyl alcohol, xylitol, malic acid, maltodextrin and modified chitosan to obtain a coating mixture; S3. The tablets obtained in step S1 and the coating mixture obtained in step S2 are subjected to a coating process. The main technical parameters of the coating process are: outlet air temperature 40-50° C., inlet air 50-60° C., spray gun pressure 0.3-0.4 MPa, and peristaltic pump 110-120 r / min.
2. A lanthanum polystyrene sulfonate sheet according to claim 1, characterized in that: In step (2), the material is crushed in a jet mill with a feed rate of 0.30.8 kg / h and a crushing pressure of 12 MPa.
3. A lanthanum polystyrene sulfonate sheet according to claim 1, characterized in that: The filler is one or more of mannitol, maltose, glucose, lactose and dextrin.
4. The lanthanum polystyrene sulfonate sheet according to claim 1, characterized in that: The flavoring agent is one or more of mint flavor, strawberry flavor, watermelon flavor, orange flavor and pineapple flavor.
5. The lanthanum polystyrene sulfonate sheet according to claim 1, characterized in that: The lubricant is one or more of talc, magnesium stearate, calcium stearate, polyethylene glycol and magnesium lauryl sulfate.
Citation Information
Patent Citations
Nano lanthanum carbonate and orally disintegrating tablet and preparation method
CN101077338A
Lanthanum carbonate orally-disintegrating tablet and preparation methods thereof
CN110664769A